The Periodicals in Bulgaria – Contemporary Market Asymmetries (2010 – 2012) - Tsankova, Svetla (Research Papers, 2014)
The trends in the Bulgarian print media market from the previous decade continue during the period of 2010-2012. There is a lack of transparency of media ownership and financing, oligopolistic market structure, unfair competition, strong political dependency, limited pluralism, unification of media content, furthering of the position of tabloids and the mainstream press going gutter, withdrawal of the readers, decrease of the circulation, the advertisement revenues lessen year after year, the self-regulation is ineffective.According to unofficial sources, the process of ownership concentration in the newspaper business continues, so does the ownership of the distribution channels. The oligopolistic structure of both newspapers and magazines markets sharpens the competition among the publishing houses and the struggle for readers and advertisers grows bitter as supply exceeds demand. Those trends uncover market asymmetries that could be fatal to the traditional press. Creating a healthy environment for the development of the periodicals in Bulgaria is a responsibility of the publishers but also of some national institutions. The market logic has to overcome the political and economic dependency of the press in order to generate much more diverse content of high quality and to prevent the final transfer of the readership to the growing online media.